Tweeting in the Courtroom: a revolution in judicial journalism - Azurmendi, Ana (2014)
The increasing number of electronic mobile devices like tablets and smartphones, with capacity to tape and report audiovisual contents, has made a considerable impact in reporter’s work. The possibility of taping live images without having to move a TV camera in courtroom, o even better, being able to transmit news, perceptions or opinions during judicial proceedings by Social Media (over all Twitter) not only has changed the way in which journalists work, but it has also suppose a series of benefits and risks for the judicial proceeding itself. In the same way that in the late 1990s, the O. J. Simpson trial (USA) wasthe reference for the debate on the access of TV cameras in Courts, today, the Oscar Pistorius (South Africa) is the field of proofs to visualize those changes that Twitter has introduced in the journalistic coverage of Courts.